1961
DOI: 10.1037/h0093825
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memorization of classifications.

Abstract: The present study explores some of the factors that determine how difficult a classification will be to learn or remember. By a "classification" we mean, here, simply a grouping of a given set of stimuli into two or more mutually exclusive and exhaustive classes. The learning or memorization of a classification can be regarded as a process of associating, to each stimulus, a certain response. This response might be the verbal label arbitrarily assigned to the class containing that stimulus, or it might be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
1,188
4
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 708 publications
(1,250 citation statements)
references
References 37 publications
52
1,188
4
6
Order By: Relevance
“…More work needs to be done in order to model category intuitiveness in a satisfactory way. For example, with the Shepard, Hovland, Jenkins (1961) data, the unsupervised GCM performed better than both the simplicity model and the rational model. In the case of the 5-4 category structure (Medin & Schaffer, 1978), the simplicity model came out ahead, with the unsupervised GCM providing the second best fit.…”
Section: Discussionmentioning
confidence: 98%
“…More work needs to be done in order to model category intuitiveness in a satisfactory way. For example, with the Shepard, Hovland, Jenkins (1961) data, the unsupervised GCM performed better than both the simplicity model and the rational model. In the case of the 5-4 category structure (Medin & Schaffer, 1978), the simplicity model came out ahead, with the unsupervised GCM providing the second best fit.…”
Section: Discussionmentioning
confidence: 98%
“…Medin et al, 1987). Similarly, Combination Theory predicts that single-dimension category structures are generally learned more quickly than multiattribute category structures (Shepard et al, 1961) -the assumption is that participants test the lowest effort, single-dimension, hypotheses first (cf. Nosofsky et al, 1994).…”
Section: Evidence For Combination Theorymentioning
confidence: 99%
“…Love (2002) reported that, under incidental conditions, a particular type of overall similarity classification, a Type IV problem (Shepard et al, 1961), was easier to learn than an exclusive-or classification in which one stimulus dimension was irrelevant (a Type II problem).…”
Section: Limitations and Extensionsmentioning
confidence: 99%
“…Rosch, Mervis, Gray, Johnson, & Boyes-Braem, 1976;Ross & Murphy, 1999;Medin et al, 2005), or understanding category learning using artificially constructed stimulus sets (e.g. Shepard et al, 1961). Studies of real-world domains have shown that people learn richly structured categories, and have identified cross-cutting systems of categories in several domains.…”
Section: Empirical Evidence For Cross-cutting Systems Of Categoriesmentioning
confidence: 99%
“…Love, Medin, & Gureckis, 2004;Medin & Schaffer, 1978;Nosofsky, 1984;Shepard, Hovland, & Jenkins, 1961). The second alternative formalizes the intuition that people's cross-categorization behavior arises as a consequence of successive attempts to account for poorly explained features.…”
mentioning
confidence: 99%